NT-proBNP as an Additional Marker of Significant Coronary Atherosclerotic Lesions - Oksana Yu. Marchenko; Nadiya M. Rudenko; Yana Yu. Dzhun (Ukrainian Journal of Cardiovascular Surgery, 2021)
Coronary artery disease (CAD) is the leading cause for morbidity and mortality both in Ukraine and in the world, so the relevance of this problem for the society is undeniable. The priority is still to study the factors that affect both more severe CAD in patients with chronic coronary syndrome and after myocardial revascularization.The aim. To investigate the patterns of correlation between blood level of N-terminal pro-B-type natriuretic peptide (NT-proBNP) and CAD severity, especially in patients with multivessel lesion, to confirm its status of a useful additional marker for assessing the condition of cardiovascular system and one of the instruments to affect the tactics of treatment.Materials and methods. The study is based on data obtained from a prospective analysis of 40 patients at the age of 51 to 82 years old from January to December 2019, whose complaints could indicate the CAD. All the patients underwent a comprehensive clinical and laboratory examination (complete blood count, biochemical blood test). The main instrumental examination method was coronary angiography; the patients were divided into 2 groups on the basis of the examination results. The quantitative degree of lesion was assessed using the SYNTAX Score for each patient.Results. The groups were comparable in terms of age, sex, and comorbidities. The groups differed significantly in terms of body mass index. Moreover, the groups differed in the level of the following biochemical markers: NT-proBNP (p=0.0001), cholesterol (p=0.02), low-density lipoproteins (p=0.009), creatinine (p=0.02), glomerular filtration rate (p=0.08). A significant correlation was found between the NT-proBNP level and the degree of CAD ρ=0.718 (p=0.0001).Conclusion. NT-proBNP significantly correlates with the SYNTAX Score and is the highest in the group of patients with multivessel coronary disease. This indicator requires further study as an additional marker for assessing the state of the cardiovascular system and can influence the choice of treatment.